Penerapan Prinsip Kesetaraan dalam Pemberian Hak Bagi Peserta BPJS Kesehatan Berdasarkan Peraturan Presiden Nomor 82 Tahun 2018 tentang Jaminan Kesehatan (Universitas Islam Balitar, Blitar, 2022)
This normative legal research is relevant to answering the legal issue of health insurance policies. The application of the principle in various policies of social health insurance services or between one policy and another in Indonesia is appropriate. These policies are Law Number 40 of 2004 concerning the National Social Security System, Law Number 24 of 2011 concerning the Social Security Administering Body, Government Regulation Number 76 of 2015 concerning Amendments to Government Regulation Number 101 of 2012 concerning Recipients of Health Insurance Contribution Assistance , Presidential Regulation Number 82 of 2018 concerning Health Insurance, and Regulation of the Social Security Administering Body Number 1 of 2014 concerning the Implementation of Health Insurance. However, in Presidential Regulation Number 82 of 2018 concerning Health Insurance, there is a sense of injustice for the community due to differences in health services that cannot be covered by BPJS Health, such as health services due to criminal acts of persecution, sexual violence, victims of terrorism and criminal acts of trafficking in accordance with statutory regulations.